(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Abstract: The growing demand for nutritionally enhanced foods reflects a broader trend toward health and wellness among consumers. The market success of these products hinges not only on their nutritional benefits but also on consumer perception. This paper examines the impact of consumer perception on the market demand for nutritionally enhanced foods from a commercial perspective. It explores how factors such as cultural beliefs, health awareness, marketing strategies, and consumer trust shape attitudes toward these products. The role of marketing in educating and influencing consumers is highlighted, along with the importance of transparency and authenticity in brand messaging. Consumer trends such as personalized nutrition and the wellness movement are identified as key drivers of market demand. The paper also addresses challenges like consumer skepticism and premium pricing, offering strategies for businesses to enhance market acceptance. By focusing on product innovation, targeted marketing, and consumer education, companies can effectively tap into the growing demand for nutritionally enhanced foods, fostering positive consumer perceptions and driving commercial success.